Assessing effectiveness of drought tolerance indices in selecting grape (Vitis vinifera) under induced drought stress conditions - PRAKASH, JAI; S, AMULYA; VERMA, M K; SINGH, SANJAY K; BHARADWAJ, C; THAKRE, MADHUBALA; KUMAR, CHAVLESH; C J, YOGESH BABU (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2021–23 at ICAR-Indian Agricultural Research Institute, New Delhi, focusing on 10 diverse grape (Vitis vinifera L.) genotypes [Pusa Navrang (PN), Pusa Aditi (PA), Pusa Trisha (PT), Pusa Swarnika (PS), Pusa Purple Seedless (PPS), Flame Seedless (FS), St. George (SG), Dog Ridge (DR), V. parviflora (VP), and Male Hybrid (MH)] for their response to controlled moisture stress (21 days) and well-watered conditions in plastic pots (14) maintained under polyhouse conditions. Drought decreased plant height differently among genotypes (9.71–41.68%). Dogridge had the highest root: shoot ratio (0.79), St. George showed lower (0.44) in response to drought. Drought tolerance indices identified genotypes Vitis parviflora (VP), Pusa Navrang (PN), Male Hybrid (MH) and Dogridge (Vitis × champini) (DR) as more drought-tolerant, while Pusa Trishar (PT) and Flame Seedless (FS) were susceptible. Cluster analysis showcased distinct differences among genotypes, while principal component analysis (PCA) emphasized key indices predicting performance in varying conditions with 98.91% variance for plant height and 99.10% variance for index root: shoot ratio contributed from two primary principal components (PC1 and PC2). Correlations (P<0.001) highlighted the predictive value of specific indices, like the drought resistance index (DI), mean relative performance (MRP), stress tolerance index (STI) and relative efficiency index (REI) for drought tolerance. The above-identified genotypes were validated through multivariate stability trait index analysis outlining their utility as donor parents/rootstocks. In conclusion, the study underscores genetic diversities as pivotal in determining drought tolerance in grape genotypes. It has generated valuable insights for selecting drought-resistant genotypes which could contribute to sustainable viticulture under the changing climate situations.